A Study of Fine Needle Aspiration Cytology of Breast Lump With The Use of National Health Service Breast Screening Program (NHSBSP) - Study Of 500 Cases - Shahu, Neha Shivkanth; Gamit, Bhavna Nilesh; Sheth, Sheetal Pankajbhai; Sutariya, Sweta Ashokbhai; Kukadiya, Harshal Harsukhbhai (Annals of Pathology and Laboratory Medicine, 2022)
Background: FNAC is rapid, simple, safe, cost effective and good screening procedure with high sensitivity and specificity. Clinically, the diseases of breast mainly present as palpable breast lump, pain and nipple discharge. Most of the breast lumps are benign but pose a significant anxiety to the patient, which can be allayed by giving assurance that, usually it is benign. So it is necessary to distinguish benign from malignant conditions Methods: The present study on was carried out during June 2017 to May 2019. We categorized the patients into C1 (Inadequate), C2 (Benign), C3 (Atypia, probably benign), C4 (Suspicious of malignancy) and C5 (Malignant) category according to NHSBSP and correlated histopathologically whenever available. Result: Total 500 cases examined. Majority of the cases were in the 3rd decade of the life. Benign category comprised of 368 cases (73.6%), followed by malignant disease 61 (12.2%). Fibroadenoma was most common comprising of 230 cases (62.3%) among benign cases. Out of 230 cases of Fibroadenoma, most (89) cases were in 21-30 years age group, followed by 11-20 years age group. Breast carcinoma was most common (31.1%) in 41-50 years age group and 61-70 (27.9%) years age group followed by 51-60 (19.7%) years age group. Conclusion: FNAC of breast lesions is advantageous for both clinicians and patients because of its immediate results, economy, and accuracy. FNAC has got significant diagnostic value in differentiating benign from malignant lesions providing us valuable information for planning of subsequent therapeutic management and avoiding unwanted surgeries.